2013
DOI: 10.4014/jmb.1205.05018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics Lactobacillus and Bifidobacterium on Gut-Derived Lipopolysaccharides and Inflammatory Cytokines: An In Vitro Study Using a Human Colonic Microbiota Model

Abstract: Gut-derived lipopolysaccharides (LPS) are critical to the development and progression of chronic low-grade inflammation and metabolic diseases. In this study, the effects of probiotics Lactobacillus and Bifidobacterium on gut-derived lipopolysaccharide and inflammatory cytokine concentrations were evaluated using a human colonic microbiota model. Lactobacillus reuteri, L. rhamnosus, L. plantarum, Bifidobacterium animalis, B. bifidum, B. longum, and B. longum subsp. infantis were identified from the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 50 publications
4
80
0
3
Order By: Relevance
“…The exact mechanism by which probiotics work has also been investigated extensively. An in-vitro study showed that bifidobacterium reduces the colonic lipopolysaccharide and hence decreases the proinflammatory state 6 . Bifidobacterium has been reported to significantly decrease the symptoms of irritable bowel syndrome and reduce the frequency of acute infectious diarrhoea 7 8…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which probiotics work has also been investigated extensively. An in-vitro study showed that bifidobacterium reduces the colonic lipopolysaccharide and hence decreases the proinflammatory state 6 . Bifidobacterium has been reported to significantly decrease the symptoms of irritable bowel syndrome and reduce the frequency of acute infectious diarrhoea 7 8…”
Section: Discussionmentioning
confidence: 99%
“…In fact, existing preclinical data provides direct evidence in support of this in a model where probiotic supplementation after the neurotrauma significantly lowered the intestinal permeability that was otherwise increased by the damage to the intestinal mucosa following TBI 118 . These findings suggest that probiotics can fortify the intestinal barrier to mitigate neurotrauma induced endotoxemia and inhibit systemic dysregulation of the immune system that may otherwise peripherally hyper-activate the brain's microglia [187][188][189] . This is supported by emerging evidence from multiple experimental models further suggests that probiotic supplementation may have protective role against LPS induced neurodegeneration 178,179 .…”
Section: Targeting the Microbiotamentioning
confidence: 95%
“…Previous research has established the efficacy of APA microencapsulation as an effective delivery system to maintain the cell viability of B. infantis ATCC 15697 in the colon [21]. In addition, in vitro studies have demonstrated that B. infantis administration to the gut microbiota modulated gut bacterial populations towards reduced colonic endotoxins concentrations [19]. Endotoxins are potent immunomodulatory components derived from the cell wall of Gram-negative bacteria that can enter the blood circulation and cause metabolic endotoxemia [5–7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies performed by our group have already demonstrated the potential of Bifidobacterium longum subsp. infantis ( B. infantis ) ATCC 15697 to modulate simulated human gut microbiota towards reduced colonic endotoxins concentrations [19]. The present study investigates the use of orally delivered alginate-poly-L-lysine-alginate (APA) microencapsulated B. infantis ATCC 15697 to modulate the gut microbiota composition and reduce endotoxemia in F344 conventional rats.…”
Section: Introductionmentioning
confidence: 99%